Stock Valuation Of Mining Sector Companies Listed In Idx Using Dividend Discounted Model (Ddm), Price To Earning Ratio (Per), Price To Book Value Ratio (Pbv), And Price To Sales Ratio (Per) - Lotisna, Devi Nadia; Sobarsyah, Muhammad; Dewi, Andi Ratna Sari (Jurnal Mirai Management, 2023)
This study is conducted to analyze the intrinsic value of companies in mining sector using absolute valuation method of Dividend Discounted Model (DDM), and relative methods consisted of Price TO Earning Ratio (PER), Price to Book Value (PBV), Price to Sales (P / S) using financial reports of mining sector companies listed on Indonesia Stock Exchange in 2020 – 2022. Based on the results of this study, the author develop Investment decisions for mining sector companies by considering recommendations from the stock valuation analysis that has been reviewed. This study recommends to buy ADRO, BSSR, PTBA, ITMG, KKGI,TBMS, ANTM, TPMA that are estimated undervalued and sell for the rest that are estimated overvalued but with specifics for trading or long term investments. Keyword : mining sector, dividend discounted model, price earning ratio, price to book value, price to sales, stock valuation.